Azzain Grocery Store Management System - Muhammed Hazim Abhar Mohamed Azahar; Selamat, Norhanim; Muhammad Zaim Junaidi Azhar (Applied Information Technology And Computer Science, 2023)
Grocery stores play an important role in the community by providing goods and services that people need every day. Acting as intermediaries between wholesalers and customers, grocery stores facilitate the exchange of goods. Effective management is essential to the store’s success, as it can help create a positive work environment, improve employee morale, and increase customer satisfaction. Therefore, a grocery store management system was developed for Azzain Grocery Store business. This system aims to streamline various business activities, including inventory management, sales transaction management, and the generation of daily sales reports. All management activities will be conducted digitally, utilizing a web-based approach. The grocery store management system utilized Vue.js for the user interface and Node.js for the backend. An iterative model was adopted, enabling continuous development and improvement. The system’s implementation is expected to alleviate the burden on employees and managers, promoting smoother business management.